5(x-1)-3=x-2

Simple and best practice solution for 5(x-1)-3=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)-3=x-2 equation:



5(x-1)-3=x-2
We move all terms to the left:
5(x-1)-3-(x-2)=0
We multiply parentheses
5x-(x-2)-5-3=0
We get rid of parentheses
5x-x+2-5-3=0
We add all the numbers together, and all the variables
4x-6=0
We move all terms containing x to the left, all other terms to the right
4x=6
x=6/4
x=1+1/2

See similar equations:

| 2×k=6 | | 10^(x)=1,000,000 | | -6+8(x+4)=-6x+2(x+7) | | (X+3/2)-(3x-1/4)=1 | | 3(x+2)+5=4 | | 30x6-0.6=10.24 | | 5(2x+4)-4x=44 | | h=30T-0.6 | | 4x+6x-44=66-9x | | 2(2x-3)+6x=24 | | 20x+5=2x-13 | | 0.13x+0.7(x-5)=0.01(2x-5) | | 1,2x+15=15 | | 7.71=2(3.14)r | | 2(x+4)+3=-5(x+1) | | (x+4)^2=225 | | 162=6(x-2) | | 17+2,5x=32 | | 4p-p=5-2 | | 175m−100m+48,750=50,500−175m | | x+1/6x=25 | | 12x^2-x-426=0 | | |x-4|+|2x-1|=|x|+3 | | 12-|x-3.5|=19 | | 5(2x-3)=6-5x | | 7+y/3=10 | | 12=3(x+6)-6x | | 2+3×-6=x+3 | | 4w+6÷2=19 | | X+7+x×3=47 | | 3x-6=2x+24 | | 4/5b+2/15=8/3b |

Equations solver categories